Implementasi Aplikasi Multimedia Interaktif Dalam Pembuatan Game Edukasi Pengenalan Perangkat Keras Komputer - Elsen, Rickard; Tazudin, Ridwan (Institut Teknologi Garut, 2025)
The development of information technology has brought significant changes to education, particularly through the use of multimedia technology. Multimedia technology enables the presentation of information in a more engaging and effective way by combining text, sound, and images in an interactive format. Educational games have become one of the most appealing innovations in this context, including games for introducing computer hardware. However, limited facilities in some educational institutions pose challenges in delivering learning materials. Teachers and students often rely solely on textbook images due to the lack of available computer hardware and supporting technology. This study aims to design and implement an interactive mobile-based multimedia application for an educational game introducing computer hardware.The method used in this research is based on the Multimedia Development Life Cycle (MDLC) approach, which involves the stages of Concept, Design, Material Collecting, Assembly, and Distribution. The result of this research is a mobile-based educational game application for learning about computer hardware. This application can make the learning process more dynamic and engaging, and help junior high school students better understand computer hardware concepts.This research aims to contribute to innovation in teaching methods and expand students' knowledge of computer hardware.